Design of the compact, stable vertical rice seedling frame for cold regions with DLI-based dynamic light control - Guo, Lifeng; Wu, Fahui; Huang, Junjie; Wang, Yizhe; Bao, Yujian; Li, Ziliang; Wu, Yuzhu; Tang, Ru; Su, Zhongbin; Xie, Qiuju; Ma, Zheng; Wang, Liwei; et al. (International Journal of Agricultural and Biological Engineering, 2026)
Traditional flat-bed rice nurseries in cold regions require large areas and suffer from inefficient tray movement and instability. A compact vertical rice seedling frame is developed in this work, which integrates a triangular-stabilized tray support, a four-point conveying mechanism, and anti-tilt/anti-torsion features, coupled with a dynamic lighting control strategy based on daily light integral (DLI). The mechanical design was validated by finite-element analysis under design loads, and collision-free operation was confirmed by digital mock-up simulation and prototype tests. In greenhouse trials comparing the vertical frame to conventional flat cultivation, the frame increased space-use efficiency to ΔP = 119.29% (i.e., ≈19.29% higher than the flat bench), while maintaining seedling coverage at 98%±1% (ns) and stem diameter (ns), and producing significantly shorter (more compact) seedlings (p<0.05; a/b). These results demonstrate a practical pathway for high-density automated seedling production in cold climates using intelligent vertical systems. Keywords: vertical seedling frame; four-point conveying; anti-tilt rod; daily light integral; LED control; finite-element analysis; greenhouse experiment. DOI: 10.25165/j.ijabe.20261902.10316 Citation: Guo L F, Wu F H, Huang J J, Wang Y Z, Bao Y J, Li Z L, et al. Design of a compact, stable vertical rice seedling frame for cold regions with DLI-based dynamic light control. Int J Agric & Biol Eng, 2026; 19(2): 112–119.